Guinea : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper presents the results of the application of the Debt, Investment, and Growth model to the case of Guinea. The model application allows simulation of the macroeconomic implications of scaled-up investment on growth, fiscal policy, and debt sustainability. A scenario analysis comparing the results under different investment paths is also presented. The results suggest that Guinea stands to benefit substantially from scaled-up public investment. Model-based estimates suggest that the GDP per capita benefits from the authorities' public infrastructure program could be in the vicinity of 2-4 percent. However, ensuring that the expected growth and poverty reduction gains are realized requires the implementation of an accompanying fiscal strategy to preserve macroeconomic stability.